1001. NICOTIANA MEGALOSIPHON: Solanaceae. (14th August 2021) - Chase, Mark W.; Christenhusz, Maarten J. M.
Summary: Nicotiana megalosiphon is illustrated from plants cultivated at the Royal Botanic Gardens, Kew, which were grown from seeds collected near the bridge over the Mehi River near Moree, New South Wales, Australia. Its taxonomic history, ecology, cytology, etymology and cultivation are discussed. The two subspecies previously recognised within this taxon are here elevated to species level: N. megalosiphon ( sensu stricto ) and N. sessilifolia ( comb. nov .).